Prothrombotic states as risk factor of in vitro fertilization failures in women with infertility and psychosomatic disorders. - Kaminskyi, A. V.; Boychuk, O. G.; Kolomiichchenko, T. V. (Medicni Perspektivi, 2019)
Failures of in vitro fertilization (IVF) may be associated with prothrombotic states, the circulation of antiphospholipid antibodies (APA). 93 women with infertility were screened: 1 group - 32 women without severe psychosomatic disorders; 2 group - 61 women with psychosomatic disorders. The control group consisted of 30 fertile women. The level of AFA to membrane phospholipids (phosphatidylethanolamine, phosphatidylserine, cardiolipinum), antibodies to β2-glycoprotein (β2-GPI), hemostasis (platelet count, ADP-induced platelet aggregation index, fibrinogen concentration, prothrombin index, activated partial thromboplastin time - APTT, test for soluble fibrin-monomeric complexes, D-dimer), homocysteine in the blood serum was defined. The frequency of significant AFA titres in the group of women without psychosomatic disorders was 18.9%, and if they were present - 44.3%, the rate of β2-GPI 9.6% versus 24.5%, respectively. Only in 11.5% of women in 2 groups, elevated levels of APA were associated with β2-GPI and/or one or more clinical criteria for antiphospholipid syndrome (APS). In patients with infertility and psychosomatic disorders, increased platelet aggregation in the context of relative thrombocytopenia, higher fibrinogen levels, soluble fibrin-monomeric complexes, and prolonged APTT with elevated D-dimer levels was revealed. Some patients have hyperhomocysteinemia. Factors that adversely affect the efficiency of IVF in the patients with psychosomatic disorders were noted: elevation of APA; reduction in the number of platelets; growth of the ADP-induced aggregation index; extension of APTT; increase of fibrinogen, D-dimer; homocysteine. The presence of prothrombotic states associated with APS should be taken into account when preparing for IVF and perform their appropriate correction.